Combining satellite observations and reanalysis energy transports to estimate global net surface energy fluxes 1985–2012. Issue 18 (28th September 2015) - Liu, Chunlei; Allan, Richard P.; Berrisford, Paul; Mayer, Michael; Hyder, Patrick; Loeb, Norman; Smith, Doug; Vidale, Pier‐Luigi; Edwards, John M.
Abstract: Two methods are developed to estimate net surface energy fluxes based upon satellite‐derived reconstructions of radiative fluxes at the top of atmosphere and the atmospheric energy tendencies and transports from the ERA‐Interim reanalysis. Method 1 applies the mass‐adjusted energy divergence from ERA‐Interim, while method 2 estimates energy divergence based upon the net energy difference at the top of atmosphere and the surface from ERA‐Interim. To optimize the surface flux and its variability over ocean, the divergences over land are constrained to match the monthly area mean surface net energy flux variability derived from a simple relationship between the surface net energy flux and the surface temperature change. The energy divergences over the oceans are then adjusted to remove an unphysical residual global mean atmospheric energy divergence. The estimated net surface energy fluxes are compared with other data sets from reanalysis and atmospheric model simulations. The spatial correlation coefficients of multiannual means between the estimations made here and other data sets are all around 0.9. There are good agreements in area mean anomaly variability over the global ocean, but discrepancies in the trend over the eastern Pacific are apparent. Key Points: Net surface energy flux is reconstructed from satellite data and reanalyses High correlation between multiannual mean reconstruction and simulations Reduced heating of East Pacific Ocean 1986–2008 at odds with simulations